(untitled) (Clinics, 2013)
OBJECTIVE: Mammography has been established as the gold standard for the detection of breast cancer, and imaging techniques such as ultrasonography, magnetic resonance imaging, scintigraphy and positron emission tomography may be useful to improve its sensitivity and specificity. The objective of this study with breast scintigraphy was to evaluate the uptake of 99mTc-thymine in mammary lesions. METHODS: A total of 45 patients were included in this study. Thirty-three patients (73%) were subjected to surgery or percutaneous biopsy, providing histopathological data. The other 12 patients who remained under surveillance received clinical examinations and biannual mammography with a normal follow-up of at least three years, the data from which were used for comparison with the scintimammography results. RESULTS: The majority of patients (64.4%) had clinically impalpable lesions with a mammogram diagnosis of microcalcifications, impalpable nodules, or focal asymmetry. Of the studied lesions, 87% were smaller or equal to 20 mm in diameter, and 22% had malignant histopathological findings. Scintigraphy with 99mTc-thymine had a sensitivity of 70%, a specificity of 85.7%, positive and negative predictive values of 58.3% and 90.9%, respectively, and an accuracy of 82.2%. CONCLUSIONS: The results of this study are consistent with those previously reported by other authors. The good specificity and high negative predictive value of this technique and the absence of uptake in the heart indicate that it may be a promising complementary method in clinical practice and that it may contribute to reducing unnecessary benign biopsies.